Procedural modeling of architecture with round geometry. (May 2017) - Edelsbrunner, Johannes; Havemann, Sven; Sourin, Alexei; Fellner, Dieter W.
Highlights: A procedural 3D modeling method using different coordinate systems is shown. It uses common splitting operations that orient along the coordinate systems. An optional high-level input is possible to align procedural components. Graphical abstract: Abstract: Creation of procedural 3D building models can significantly reduce the costs of modeling, since it allows for generating a variety of similar shapes from one procedural description. The common field of application for procedural modeling is modeling of straight building facades, which are very well suited for shape grammars—a special kind of procedural modeling system. In order to generate round building geometry, we present a way to set up different coordinate systems in shape grammars. Besides Cartesian, these are primarily cylindrical and spherical coordinate systems for generation of structures such as towers or domes, that can procedurally adapt to different dimensions and parameters. The users can apply common splitting idioms from shape grammars in their familiar way for creating round instead of straight geometry. The second enhancement we propose is to provide a way for users to give high level inputs that are used to automatically arrange and adapt parts of the models.